Building resilience capacity through innovation: highlights from European reports - Fernandes, Silvia Brito (2014)
More than ever firms will be required to develop strategies for coping with shocks and stresses to our economic and social infrastructures. They will need to build the so called resilience capacity, which is an umbrella term for the planning and design strategies that can help firms develop the capacity to cope with challenges. The present work is based on an assessment of works that explored recent European reports on innovation performance. The discussion acknowledges that firms will have to find new ways to reduce their risk-aversion and become more flexible. To become more resilient, firms will need to adopt strategies that allow them to develop capacities that better respond and adapt to the economic and social stresses. These capacities must be planned to transform our current economic systems into much more flexible and dynamic ones. Small and medium enterprises are more exposed to competitive pressures. Thus, the choice of sectors and the design of public procurement policies are fundamental opportunities. With the polarization of knowledge creation across Europe, a few countries are responsible for the bulk of innovation and knowledge production. Therefore, attention should also be given to investment in knowledge diffusion and absorption depending on the specific national context. The fact of some characteristics of the national innovation system explain persistence on innovating in response to major external shocks sheds light on the resilient behavior of firms.